Transvernacular Poetry and Government: Andrew Marvell in Early Modern Europe. Issue 1 (15th August 2017) - Smith, Nigel
Abstract : Marvell's experiences as traveling tutor, diplomat and political agent add a dimension of real international encounter in his poetry and prose that stands in addition to the literary citation or quotation of non-English books, and makes his verse distinctive among his contemporaries. This essay maps some of the literary landscape and the politics of literature in the places he visited in Europe, Russia and Scandinavia, and not least the monarchical absolutism experienced by some writers in these places. While some of this encounter and literary knowledge is reflected in his writing, other parts are not. The dominant pattern is that the north European encounter is in general not met by northern literary influence in Marvell's writing: features of citation, quotation, allusion and echo are largely to southern European sources: mostly French and Italian, but also Spanish. Marvell's interest in the longer history of lyric is set in the context of the Thirty Years War that seriously inhibited access to valuable ancient manuscripts. The question of the possible influence of some of Marvell's writings, especially his poetry, in seventeenth-century Europe is discussed. It is to be hoped that the geography of poetry begun here will help illuminate the European dimensions of Marvell's writings as more concrete details of his activities and his writings in Europe as well as in England are discovered.